Increased Concrete Strength with the Addition of Hyacinth Natural Fibers - Losita Dewi; Dewanto; Santi Mareta; Destra Amni; Sisi Yulianti; Delfi Kurnia Zebua; Wiwid Suryono; Tomi Apra Santosa; Mohammad Edy Nurtamam (LPPM Akademi Teknik Adikarya, 2023)
Concrete is a brittle and fragile construction material so it needs to be increased in strength. This study aims to increase the strength of concrete by adding natural fibers of water hyacinth to the concrete mixture. Hyacinth fibers are cut by 3-5 cm and added with variations of 0%, 0.1%, 0.2%, 0.3%, 0.4% and 0.5% of the volume of concrete. Cylindrical specimens 15 cm in diameter and 30 cm in height were tested for compressive strength and tensile strength at the age of 28 days. The test results showed that the addition of hyacinth fiber up to 0.5% increased the compressive strength of concrete up to 17.6% and tensile strength up to 71.4% compared to normal concrete without fiber. The increase in strength is due to hyacinth fibers being able to withstand micro-cracks in concrete. The more fiber added, the more microcracks are able to be prevented thereby increasing the strength of concrete. In conclusion, the natural fiber of hyacinth effectively increases the strength of concrete both in compressive and tensile capacity.